2005
DOI: 10.1104/pp.105.067546
|View full text |Cite
|
Sign up to set email alerts
|

The Polygalacturonase-Inhibiting Protein PGIP2 of Phaseolus vulgaris Has Evolved a Mixed Mode of Inhibition of Endopolygalacturonase PG1 of Botrytis cinerea

Abstract: Botrytis cinerea is a phytopathogenic fungus that causes gray mold in .1,000 plant species. During infection, it secretes several endopolygalacturonases (PGs) to degrade cell wall pectin, and among them, BcPG1 is constitutively expressed and is an important virulence factor. To counteract the action of PGs, plants express polygalacturonase-inhibiting proteins (PGIPs) that have been shown to inhibit a variety of PGs with different inhibition kinetics, both competitive and noncompetitive. The PG-PGIP interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 51 publications
3
81
1
1
Order By: Relevance
“…The crystal structure of F. moniliforme FmPG1 showed that this protein has two additional loops that form a lid over the active site, causing the substrate-binding cleft to become narrower [28]. This lid is absent in other PGs, such as B. cinerea BcPG1 [29 ], and may have evolved to prevent binding of substrate-mimicking inhibitors.…”
Section: Wheat Inhibitor Xip-i Targets Fungal Gh11 and Gh10 Xylanasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structure of F. moniliforme FmPG1 showed that this protein has two additional loops that form a lid over the active site, causing the substrate-binding cleft to become narrower [28]. This lid is absent in other PGs, such as B. cinerea BcPG1 [29 ], and may have evolved to prevent binding of substrate-mimicking inhibitors.…”
Section: Wheat Inhibitor Xip-i Targets Fungal Gh11 and Gh10 Xylanasesmentioning
confidence: 99%
“…However, predicting interactions between PG and PGIPs is not straightforward since PGIPs appear to bind PGs in different orientations [30 ]. PvPGIP2 is a competitive inhibitor of FmPG1 but it inhibits BcPG1 in a noncompetitively mixed mode, allowing the substrate to bind with reduced affinity and reduced kinetics of hydrolysis [29 ]. Docking studies of PvPGIP2 with a model of BcPG1 indicates that PvPGIP2 binds BcPG1 in a different orientation, allowing the substrate to interact (Figure 2f) [29 ].…”
Section: Detailed Analysis Of the Pgs Of Fusarium And Beanmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases a single PGIP isoform inhibits different PGs with a different mechanism, i.e. competitive, noncompetitive, and/or mixed (King et al, 2002;Sicilia et al, 2005;Bonivento et al, 2008). Genes encoding PGIPs are under selective pressure for diversification and a number of hot spots for the interaction with PGs have been identified on the inhibitor concave surface and validated by site-directed mutagenesis (Casasoli et al, 2009).…”
mentioning
confidence: 99%
“…Moreover, a single PGIP is often capable of inhibiting different fungal PGs with different mechanisms: for example PGIP2 from Phaseolus vulgaris (PvPGIP2) inhibits Fusarium moniliforme PG (FmPG), Aspergillus niger PGII (AnPGII), and Botrytis cinerea PG1 with a competitive, noncompetitive and mixed mode of action, respectively. [10][11][12] We have determined the crystal structure of a PG from the phytopathogenic fungus Colletotrichum lupini (CluPG1), the causal agent of lupin anthracnose. Moreover we have characterized its enzymatic activity, analyzed the inhibition mode exerted by PvPGIP2 on the enzyme and compared our data with those on AnPGII and FmPG, whose 3D structures and inhibition kinetics are already known.…”
Section: Introductionmentioning
confidence: 99%